Dynamic symmetrization in a memristive HR neuron - Keyu Huang; Chunbiao Li; Yongxin Li; Tengfei Lei; Haiyan Fu (Electronics Letters, 2024)
Abstract The significance of neuronal discharge symmetry lies in its reflection of the stability and orderliness within the neuron's activity. This symmetry is correlated with various issues, including the biophysical properties within neurons, network structures, and synaptic transmission. Memristors are highly analogous to neuronal synapses due to their unique memory properties, allowing them to emulate biological neural synapses. In this work, a memristor is employed into the Hindmarsh‐Rose (HR) neuron as a synapse for the construction of a memristive HR neuron. Accompanied with the introducing of the absolute value and signum function, the derived neurons exhibit complex coexisting symmetric firing patterns. The phenomenon of symmetric firing can effectively simulate the depolarization and hyperpolarization processes of neurons, providing a new approach to study the diversity of the brain.